Causes of Acute Peritonitis and its Outcome in Tertiary Medical Centre - Malik, Mariam; Iqbal, Mazhar; Magsi, Abdul Malik; Parveen, Sughra; Khan, Muhammad Iqbal; Shamim, Munazza; Malik, Shoaib (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine the factors causing peritonitis and deaths at Jinnah Hospital Karachi. METHODOLOGY: The study included 216 patients with acute peritonitis who underwent exploratory laparotomy from 2016 to 2018. Surgical treatment according to cause and post-operative treatment of disease carried out. Histopathological report and other diagnostic test like typhoid dot test and blood culture results were recorded and resultwas analyzed by SPSS version 24. RESULTS: Frequent causes of acute peritonitis were typhoid intestinal perforation 62(28.70%),Peptic ulcer perforation 54 (25%), rupture appendix 38 (17.59%), tuberculous intestine perforation 26 (12.05%), gangrene gut 14 (6.48%), large gut tumor perforation 10 (4.62%), ruptured liver abscess 4 (1.85%), ruptured gall balder 4 (1.85%) and acute pancreatitis 4 (1.85%). Complications were septic shock 30 (13.88%), paralytic ileus 16 (7.40%), burst abdomen 12 (5.5%) and mortality was 8 (3.70%.) CONCLUSION: Infectious diseases like typhoid, H-pylori PUD, ruptured appendix, ruptured liver abscess, and TB intestine are common causes of peritonitis.